THE EFFECTS OF OBESITY ON FEMALE PATIENTS’ REPRODUCTIVE FUNCTION IN IN VITRO FERTILIZATION (IVF) PROGRAMS - Фаткуллина, Ирина Борисовна; Сугурова, Альфия Тлешевна; Шайхлисламова, Энже Филюсовна; Садыхова, Вусала Аладдиновна; Далаева, Танзилла Хамидовна; Жданова, Аэллина Александровна (Mother and Baby in Kuzbass, 2025)
Due to the multifaceted impact of obesity on women’s reproductive function, as well as the outcomes of assisted reproductive technology (ART) programs, there is an urgent need to study the impact of this disease and find ways to solve this problem in women with infertility planning ART programs. This review reflects the literature data showing the mechanisms of the influence of obesity on the negative outcomes of ART programs. To achieve this goal, an electronic search was conducted for literature reviews, randomized clinical trials, and meta-analyses in the Medline, PubMed, Google Scholar, Clinical Trials, and the Cochrane databases until December 2024. In the course of the work carried out, the mechanisms influencing the effectiveness of ART programs in obese patients were identified: adipose tissue is an inflammatory substrate, as a result of chronic inflammation it enhances the synthesis of reactive oxygen species. Reactive oxygen species reduce the quality of oocytes and, consequently, the quality of embryos. This pushes reproductive doctors to pay more attention to pre-pregnancy training of obese patients before ART programs.